Mobilization of hematopoietic progenitor cells for autologous transportation: consensus recommendations - Duarte,Fernando Barroso (2016)
SUMMARY Selected patients with certain hematological malignancies and solid tumors have the potential to achieve long-term survival with autologous hematopoietic progenitor cell transplant. The collection of these cells in peripheral blood avoids multiple bone marrow aspirations, results in faster engraftment and allows treatment of patients with infection, fibrosis, or bone marrow hypocellularity. However, for the procedure to be successful, it is essential to mobilize a sufficient number of progenitor cells from the bone marrow into the blood circulation. Therefore, a group of Brazilian experts met in order to develop recommendations for mobilization strategies adapted to the reality of the Brazilian national health system, which could help minimize the risk of failure, reduce toxicity and improve the allocation of financial resources.